Heel Pain in a Young Athlete – Haglund’s Disease - Komar, Olga; Kochański, Marek; Pokrywka, Natalia; Szymańska, Kinga; Suwała, Dawid; Barczak, Iga; Gąbka , Mateusz; Trześniowska, Agata (Quality in Sport, 2026)
Haglund’s disease is a significant cause of posterior heel pain, particularly among physically active individuals. It is associated with a posterosuperior calcaneal prominence leading to irritation of the retrocalcaneal bursa and Achilles tendon. The condition has a multifactorial etiology, including anatomical, biomechanical, and environmental factors. Diagnosis is based on clinical examination and imaging modalities such as X-ray, MRI, and ultrasound. Treatment includes both conservative and surgical approaches depending on symptom severity.